2023
DOI: 10.1039/d2nj04444g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-promoted synthesis of novel N-arylamino-3,5′-biquinoline derivatives: their applications in live-cell imaging and in vitro anticancer activity evaluation

Abstract: A novel strategy for the construction of functionalized N-arylamino-3,5′-biquinoline has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Moreover, α , α ‐dicyanoolefins have been used as starting materials in vinylogous reactions, which have resulted in the creation of numerous functionalized cyclic molecules [27] . These molecules include common and complex carbocyclic and heterocyclic compounds such as isoflavones, [28] phthalimides, [29] hydroindoles, [30] polycyclic heterocycles, [31] chromene derivatives, [32] biquinolines, [33] 1,6‐naphthyridine derivatives, [34] and spirofused [35] compounds. Our research group reported the synthesis of substituted phthalimides using an ultrasound (US)‐assisted cascade reaction of 2‐(4‐oxo‐2‐thioxothiazolidin‐5‐ylidene)acetates and α , α ‐dicyanoolefins [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, α , α ‐dicyanoolefins have been used as starting materials in vinylogous reactions, which have resulted in the creation of numerous functionalized cyclic molecules [27] . These molecules include common and complex carbocyclic and heterocyclic compounds such as isoflavones, [28] phthalimides, [29] hydroindoles, [30] polycyclic heterocycles, [31] chromene derivatives, [32] biquinolines, [33] 1,6‐naphthyridine derivatives, [34] and spirofused [35] compounds. Our research group reported the synthesis of substituted phthalimides using an ultrasound (US)‐assisted cascade reaction of 2‐(4‐oxo‐2‐thioxothiazolidin‐5‐ylidene)acetates and α , α ‐dicyanoolefins [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The impressive fluorescence properties of the synthesized heterocycles also led us to investigate their biological (anti-cancer) properties in vitro, and fortunately, we achieved acceptable results. [14] The reaction of 2-chloroquinoline-3-carbaldehydes and 5-chloro-3-methyl-1-phenyl-1Hpyrazole-4-carbaldehydes with methylene active compounds has been widely studied for the synthesis of various quinolinecontaining heterocycles. [15] For example, by reacting 2-chloro-3formyl quinolines with malononitrile and, cyclic enamino ketones, a series of N-arylamino biquinoline derivatives have been synthesized that have excellent antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported the synthesis of arylamino‐3,5‐biquinolines by combining 2‐chloro‐3‐formylquinolones with a , a ‐dicyanoolefines under mild conditions (ultrasound) without using metallic reagents. The impressive fluorescence properties of the synthesized heterocycles also led us to investigate their biological (anti‐cancer) properties in vitro, and fortunately, we achieved acceptable results [14] . The reaction of 2‐chloroquinoline‐3‐carbaldehydes and 5‐chloro‐3‐methyl‐1‐phenyl‐1 H ‐pyrazole‐4‐carbaldehydes with methylene active compounds has been widely studied for the synthesis of various quinoline‐containing heterocycles [15] .…”
Section: Introductionmentioning
confidence: 99%